Pola Asuh Orang Tua dan Implikasinya Terhadap Pembentukan Karakter Anak di Kelas IV MI NW Keruak - M. Saipul Watoni (Pendidikan Al-Gafari, 2024)
Children are the next generation for the family, nation, and religion, thus children need to receive good parenting from their parents, so that when they grow and develop into adults, they will become humans who have strong personalities and have various kinds of useful abilities and skills. This study aims to determine the parenting pattern in shaping children's character and the implications of parenting patterns on children's character in Class IV MI NW Keruak. This type of research is qualitative research, a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. This research was conducted by collecting data in a reasonable state, using a systematic, directed, and accountable working method, so that it does not lose its scientific nature or a series of activities or processes of collecting data/information that is reasonable. Data collection techniques use interviews, observation methods, and documentation methods. The research analysis results show that the formation of children's character tends to be influenced by the form of parenting patterns at home. Parenting patterns can be defined as patterns of interaction between children and parents which include providing physical needs (such as eating, drinking, and others) and psychological needs (such as a sense of security, affection, and others), as well as socialization of norms that apply in society so that children can live in harmony with their environment. In other words, parenting patterns also include patterns of interaction between parents and children in the context of children's character education. It can be concluded and understood that the parenting pattern of parents towards the character formation of grade IV MI Keruak children has been done well. This is proven by the fact that children have begun to be able to speak politely and behave well to everyone, are not selfish, respect others, and are disciplined in everyday life.